The efficacy of using intraoperative compared with postoperative topical 0.04% Mitomycin-C drops to the recurrence of Pterygium - Suhardjo, Suhardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: The major problem in the treatment of pterygium is to prevent recurrences after surgical excision. To prevent the neovascularization and recurrence, variable doses and administration of mitomycin C installation had been used. However no single treatment has been universally effective yet.Objective: The purpose of this studies is to evaluate the safety and efficacy of two different methods of 0.04% Mitomycin - C application as adjunctive chemotherapy to the recurrence of pterygium. Methods: The research had been conducted at the Dr. Sardjito Central Hospital, Wates Central Hospital Gombong PKU Hospital, and Purworejo Aisyiah Hospital from January 1995 to December 1998. Eighty eight patients underwent pterygium excision were involved in this study, and divided into two groups. Group I or intraoperative 0.04% MMC group of 44 cases receiving 0.04% MMC drops applied to the bare sclera for 4 minutes intraoperatively. Group II or post operative group of 44 cases receiving 0.04% MMC eye drops one day after excision once daily during the first postoperatively week and continued with a dosage of one drop 3 times a day during the second postoperative week. Observations were done daily during the first postoperative week, weekly during the first postoperative month, and monthly up to 6 months. Observations were done including of the symptoms of recurrence and side effects of the treatment. The data were analyzed using the Students test and chi square technique.Results: In the intraoperative group, 6 cases (13.67%) recurred, 2 cases of superficial punctate keratitis. In the postoperative group,. 7 cases (15.95%), and 3 cases superficial punctate keratitis. There was no statistical difference in the rates of recurrence (x2 ---- 0,0902, p>0,05). Most of the cases of pain, tearing and lid edema occurred in the group intra-operative. No other complication was observed in the course of the study.Conclussion: A single dose intraoperative application of MMC is a simple, economic, affective alternative adjunctive treatment for pterygium.Key words : Intraoperative mitomycin-C - pterygium excision - recurrence